An Inguinal Perivascular Epithelioid Cell Tumor Metastatic to the Orbit - Zofia Tynski; Way Chiang; Albert Barrett (Hindawi Limited, 2018)
Malignant PEComas are rare mesenchymal neoplasms. These tumors harbor distinct myomelanocytic phenotype. The PEComa family of tumors includes lymphangioleiomyomatosis, angiomyolipoma, clear cell sugar tumor of the lung, and myomelanocytic tumor of the falciparum ligament/ligamentum teres. PEComas have no known normal cell counterpart. Majority of PEComas are benign and occur predominantly in the middle-age women. These tumors are commonly encountered in the uterus. Herein, we report a 20-year-old woman with a left inguinal mass metastatic to orbit, brain, lumbar spine, and skin at presentation. To our knowledge, this is the first case of metastatic PEComa to the orbit. This is the third case of primary PEComa of the inguinal area.